Supply Chain and Quality Management Practice: Its Impact on Competitive Advantage and Firm Performance (Study on Small and Medium Enterprises at West Java) - Subhan, Ali; Putro, Bramantiyo Eko (Jurnal Manajemen Teknologi, 2017)
Abstract. Small and Medium Enterprises (SMEs) play an important role in encouraging economic growth of West Java. However, the contribution of SMEs is still small due to the lack of competitiveness of SME products. Competitiveness and weak SME performance can be enhanced by supply chain management and quality management practices. This study focuses on supply chain management and quality management practices that are mutually casual, competitive advantage and firm performance and the role of moderation of company age in SMEs in West Java. The purpose of this study is to determine the effect of supply chain management and quality management practices on competitive advantage either partially or simultaneously and its impact on firm performance, and how the role of moderating variable company's age in moderating the relationship between competitive advantage and firm performance. The unit of analysis in this study is the Small and Medium Enterprises business located in West Java region with a sample size of 200 business units. To test the model of the research empirically tested using structural equation modeling (SEM) with the help of LISREL 8.70. The results of this study indicate that the implementation of supply chain management and quality management are done simultaneously provide a great impact for increasing competitive advantage as well as firm performance. The role of corporate age moderation is very small in strengthening the relationship between competitive advantages with firm performance on SMEs in West Java.Keywords: Supply chain management practice, quality management practice, competitive advantage, firm performance, firm ageAbstrak. Usaha Kecil dan Menengah (UKM) berperan penting dalam mendorong pertumbuhan perekonomian Jawa Barat. Akan tetapi kontribusi UKM masih kecil dikarenakan kurangnya lemahnya daya saing produk UKM. Daya saing dan performa UKM yang lemah dapat ditingkatkan oleh supply chain management dan quality management practices. Penelitian ini fokus pada supply chain management dan quality management practices yang saling kasual, keunggulan bersaing dan kinerja perusahaan serta peran moderasi umur perusahaan pada UKM di Jawa Barat. Tujuan penelitian ini adalah untuk mengetahui pengaruh supply chain management dan quality management practices terhadap keunggulan bersaing baik secara parsial maupun simultan dan dampaknya terhadap kinerja perusahaan, serta bagaimana peranan variabel moderating umur perusahaan dalam memoderasi hubungan antara keunggulan bersaing dan kinerja perusahaan. Unit analisis dalam penelitian ini adalah usaha Industri Kecil dan Menengah yang berada di wilayah Jawa Barat dengan ukuran sampel sebanyak 200 unit usaha. Untuk menguji model penelitian maka dilakukan pengujian secara empirik menggunakan structural equation modeling (SEM) dengan bantuan LISREL 8.70. Hasil penelitian ini menunjukan bahwa penerapan manajemen rantai pasokan dan manajemen kualitas yang dilakukan secara bersamaan memberikan dampak yang besar bagi peningkatan keunggulan bersaing maupun kinerja perusahaan. Peran moderasi umur perusahaan sangat kecil dalam memperkuat hubungan antara keunggulan bersaing dengan kinerja perusahaan pada UKM di Jawa Barat.Kata kunci: Manajemen rantai pasokan, manajemen kualitas, keunggulan bersaing, kinerja perusahaan, umur perusahaan